ANALISIS PENERAPAN SISTEM INFORMASI DOSEN DAN KARYAWAN (SIMDOSKAR) MENGGUNAKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) TERHADAP PERILAKU PENGGUNA - Yulia Rahmi; Bambang Soedijono; Hanif Al Fatta (Universitas Janabadra, 2017)
University Muhammadiyah Bengkulu (UMB) in data processing lecturers and employees have a web-based information system known as Lecturer and Employee Information System (SIMDOSKAR). This research discusses about user behavior towards SIMDOSKAR UMB using Unified Theory of Acceptance and Use of Technology (UTAUT) model. The purpose of this study is to determine the variables that affect user interest behavior and provide recommendations in the form of suggestions for improvement of the front system.This research was conducted by using descriptive qualitative method by distributing questionnaires, with 33 respondents. The data in the research were tested using SEM analysis technique and Partian Least Square (PLS) approach. The results showed that performance expectancy, effort expectancy, social influence, and attitude towards using tecknology have positive effect on User Behavior Interest. This variable is able to influence behavioral intention to use the system equal to 85,1% obtained from value of R2, whereas the lowest influence is behavior interest toward interest of user behavior with t-statistic value 0, 135. Keywords: implementation analysis, behavioral intention to use, UTAUT, SIMDOSKAR UMB